Kemiren Community Participation in Management of Kemiren Village as a Traditional and Tourism Village: Partisipasi Masyarakat Kemiren Dalam Pengelolaan Desa Kemiren Sebagai Desa Adat Dan Wisata - Leni Vitasari (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Community development is a model of intervention in social work that really pays attention to the human aspect and community empowerment, which still has a strong presence in it with educational elements that seek to change a community. The key to creating social welfare in community development is participation from the community. It is hoped that community involvement physically, mentally, materially and financially can increase the sense of togetherness and ownership of the development process and results in the community. Kemiren Village is a traditional tourist village located in Banyuwangi Regency and the village is a representation of Osing culture and customs in Banyuwangi Regency. The Kemiren Village community is a community that upholds the values ​​of Osing customs and culture, where in their daily lives they use these values ​​as guidelines, all of which are a form of local wisdom of the Kemiren Village community. This research uses qualitative descriptive data analysis techniques by obtaining data from library study observation techniques, interviews and documentation. The results obtained are that tourism development in the Osing Traditional Tourism Village is less stable seen from the fluctuating number of tourist visits, but even though it is less stable, the tourism potential in the Osing Traditional Tourism Village is interesting enough to increase tourist interest in visiting, it's just that the management must have more ability to handle tourists. Then the forms of local community participation in developing tourism in the Osing Traditional Tourism Village are: The forms of participation of the Kemiren community in developing tourism in the Osing Traditional Tourism Village are participation in decision making, participation in community participation in tourism operational activities, community participation in enjoying or utilizing the results - tourism development results, and community participation in assessing and supervising tourism activities in the Osing Traditional Tourism Village